Multibeam bathymetry raw data (Kongsberg EM 712 entire dataset) of RV MARIA S. MERIAN during cruise MSM85 - Christian Mertens; Anne-Cathrin Wölfl (PANGAEA, 2021)
Multibeam bathymetry raw data was recorded in the Atlantic during cruise MSM85 that took place between 2019-07-23 and 2019-08-13. The data was collected using the ship extquotesingles own Kongsberg EM 712. This data is part of the DAM (German Marine Research Alliance) underway research data project.